An Approach to Extract a Conceptual Model from Natural Language Specifications - Antonelli, Leandro (2023)
Requirements engineering is a critical phase in software development. Errors committed in the requirements become costly problems later on. Artifacts described in natural language are the most suitable for the participants of the process: experts and the software development team. But, natural language can have some issues because of the diversity of participants' writing and reading specifications. Thus, it is necessary to guide and assist the production of these artifacts. This paper proposes an approach to acquire specifications collaboratively checking the writing style and synthesizing a conceptual model to summarize the specification to help participants to have an overview of the knowledge gathered in order to provide a consistent and coherent model. This paper also describes a prototype that uses natural language processing and artificial intelligence tools to support the process.